PENGARUH PENGGUNAAN TEKNIK TIRU MODEL DALAM KETERAMPILAN MENULIS PUISI - M. Hafrison, Riska Oktaria Atmazaki, (Universitas Negeri Padang, 2017)
The purpose of this research is to explain the effect of the use of copy the master to the skill of writing poetry in class VIII at Junior High School 30 Padang. The kind of this research is quantitative research with experiment metode. The results of the research there are three. First, the skills of writing a poetry in class VIII SMP Negeri Padang 30 without the use of copy the master qualification either (B) with an average value of 80,39. Second, the skills of writing poetry in class VIII SMP Negeri Padang 30 by using of copy the master on the qualifications of either (B) with an average value of 84,64. Third, based on the t-test results, it was concluded that the alternative hypothesis (H1) received on the standard of 95% and dk = (n1 + n2)-2 due tcount> ttable(1,78> 1,67). Kata kunci: pengaruh, teknik tiru model, menulis puisi